Urgensi penguatan pendidikan Islam terhadap generasi Z di era revolusi industri 4.0 - Jamil, Dina Rahmatun Najma (Maliki Interdisciplinary Journal, 2024)
The industrial revolution 4.0 is referred to as the digital revolution due to the presence of computers and automated processes in all fields. This has led to significant changes on a large scale. Humans, in fulfillinf their essential needs, are heavily reliant on technology due to rapid pace of digitalization in the era of the Industrial Revolution 4.0. not only in fulfilling their life needs, but the impact of this 4.0 industrial revolution can also be observed and noted in terms of lifestyle, work, morals or ethics, education, as well as ways of socializing with each other. Education faces new challenges in the era of the industrial revolution 4.0. including Islamic education. Islamic education as a vessel for the formation of personalities and morals in accordance with Islamic values, must be able to keep up with and adapt to the progress of the world as a result of the 4.0 era. In maintaining its existence in the world of education, Islamic education is required to implement new innovation in its learning system by collaborating technology and knowledge. Teachers as facilitators for students must also be capable of keeping pace with their skills and adapting to changes in the education system that are integrated with the digital realm.